PENGOLAHAN DAN PENGEMBANGAN PRODUK DARI LIMBAH BUAH DAN BIJI SALAK DI DUSUN KEDUNG SARI DESA MRANGGEN MAGELANG - Yessi Jusman; Ahmad Zaki; wikan tyassari; Ninda Rizqi Safitri (LPPM Universitas Abdurrab, 2023)
The Kedungsari area, Mranggen, is one of the salak producers in the Magelang area. With so much production of salak fruit, a lot of waste of salak fruit and seeds is thrown away. Utilization of waste requires processing of these wastes into other products that have economic value. The service carried out has the aim of providing education to partners (Kedungsari residents) so that the salak waste can be processed into useful products for the community. At least 30 people participated in this activity, and the majority of the residents who attended were members of the Kedungsari Family Welfare Development (PKK). To expedite activities and assist the PKK in Srumbung, Mranggen was also provided with a zalacca seed grinding tool for smooth competency development and also a means of generating income for households and the community in Mranggen. Figure 2 shows a graph of the satisfaction level of residents/socialization participants. The activities carried out were training in making zalacca flesh into food products and zalacca seeds into coffee. To help make it easier for partners to process zalacca seeds, a seed grinding unit was given to partners to support villagers in processing zalacca seeds. At the implementation stage, the activities were carried out in 2 forms of training, namely training on processing zalacca fruit into food products and training on processing zalacca seeds for coffee. At least 30 people participated in this activity, with very satisfactory survey results